Novel Linkages Between Bacterial Composition of Hindgut and Host Metabolic Responses to SARA Induced by High-Paddy Diet in Young Goats - Wang, Kaijun; Yan, Qiongxian; Ren, Ao; Zheng, Mengli; Zhang, Peihua; Tan, Zhiliang; Zhou, Chuanshe (Frontiers in Veterinary Science, 2022)
Background: At present, feeding high corn diet is used to provide enough protein and energy supply to meet higher requirements to goats. In fact, because corn grain is commonly scarce in the traditional rice cropping region of southern Asia, paddy is thereby used as an alternative feed applied in the goat diets. However, the effects of the high paddy proportion on microbiota and metabolites of intestine are unclear. Here, we investigate the effects of high paddy proportion on bacterial community, potential function and metabolic reaction in the cecum of goats. Sixteen Liuyang black goats were divided into two groups and fed a normal paddy diet (NP, 55% concentrate) or a high paddy diet (HP, 90% concentrate) for five weeks. Results: Total short chain fatty acid (SCFA) concentration was higher in the hindgut chyme of the HP-fed goats than the NP-fed goats (p = 0.001). The acetic proportion was significantly decreased and propionic proportion was increased in the HP group (p < 0.05). The HP diet decreased the value of pH, lactic acid concentration, lactate dehydrogenase activity, whilst increased the activity of alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, amylase, together with lipopolysaccharide concentration in hindgut chyme of goats (p < 0.05). The abundance of Eubacterium_coprostanoligenes_group was increased (p = 0.050), whilst the abundance of Prevotellaceae_UCG_004, dgA-11_gut_group, Christensenellaceae_R-7_group, Ruminococcaceae_UCG-010 and Desulfovibrio were significantly decreased with the HP diet (p < 0.05). Conclusion: These results suggested that the HP diet altered the microbiota and metabolites, which negatively modified the health of intestinal epithelial health in goats.